The Prevalence of Reflux Esophagitis in the Elderly and Its Associated Risk Factors - Cosmas Rinaldi A Lesmana; Billy Angga; Levina S Pakasi; Waldemar Simanjuntak; Laurentius A Lesmana (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Background: Reflux esophagitis is a common problem in the elderly. Compare to the Western Countries, esophageal cancer where reflux esophagitis is the most predominant risk factor is considered rare in Asia. Many other risk factors have not been well studied especially in most Asian countries. The objective of this study is to evaluate the presence of reflux esophagitis in elderly patients and its associated risk factors.Method: This was a cross-sectional study in elderly patients who underwent upper gastrointestinal endoscopy. Patients who received long-term proton pump inhibitor (PPI) therapy, suffered from gastrointestinal malignancies, recently receiving chemotherapy agents, diagnosed with cerebrovascular disease or Helicobacter pylori infection were excluded. Statistical analyses were performed using the SPSS software version 17.00 (SPSS Inc., Chicago, Illinois, USA).Results: A total of 238 elderly patients were enrolled. Patients’ mean age was 69.8 ± 6.8 years old. Reflux esophagitis was found in 22 (9.2%) patients. Several comorbidities were found in these patients, such as diabetes, hypertension, coronary artery disease, chronic kidney disease, and liver cirrhosis. The only factor that associated with reflux esophagitis was the presence of hiatus hernia esophagus (p = 0.038). However, reflux esophagitis seemed to be more found in the elderly patients who have history of reflux inducing drugs consumption without any proton pump inhibitor (PPI) protection.Conclusion: Reflux esophagitis is still a major problem in the elderly. The presence of hiatus hernia might give an important consideration of upper gastrointestinal endoscopy screening. However, it would be a debate matter with regards to the cost burden and the low risk of esophageal cancer in Asian countries.